Faktor penghalang kepada peranan guru sebagai agen sosialisasi politik di sekolah dalam membentuk perpaduan di daerah Petaling - Yong, Hie Hie; Ku Samsu, Ku Hasnita; Adnan, Zatul Himmah (Penerbit Universiti Kebangsaan Malaysia, 2021)
Teachers are an important political socialization agent in assisting the process of fostering ethnic unity among students. At primary school level, teachers act as influential political socialization agents in nurturing awareness of students at their early age on the importance of ethnic unity especially in the context of a multi-ethnic society in Malaysia. However, the process of fostering ethnic unity in Malaysia generally, and at the primary school level in particular, is still faced with various challenges and obstacles. Hence, this paper discusses the barriers to the role of teachers as effective political socialization agents from the aspect of school administration practices in shaping ethnic unity at the primary school level. The data collection process for this study was carried out through focus group discussions method involving 16 Malay, Chinese and Indian teachers from National School (SK), The Chinese National Type School (SJKC) and Tamil (SJKT) in Petaling district, Selangor. The results found that there are three factors of administrative practices that hinder teachers in playing a role as agents of ethnic unity that can affect the process of fostering the values of unity in a school. First, teacher separation system throught double-session schooling system; second, grouping of teachers in teacher’s office by subject; and thirdly, the focus more on syllabus than other aspects such as ethnic unity in school. This study found that these three factors contribute to the existence of ethnic gaps among teachers, but also at the same time become an obstacle to the role of teachers as effective agents of ethnic unity in schools.. Hence, the school should pay attention to this issue and raise awareness of all school members on the importance of ethnic unity in the institution.makalah ini membincangkan faktor penghalang kepada peranan guru sebagai agen sosialisasi politik yang berkesan dari aspek amalan pentadbiran sekolah dalam membentuk perpaduan etnik di peringkat sekolah rendah. Proses pengumpulan data bagi kajian ini dijalankan melalui kaedah perbincangan kumpulan berfokus yang melibatkan 16 orang guru Melayu, Cina dan India daripada Sekolah Kebangsaan (SK), Sekolah Jenis Kebangsaan Cina (SJKC) dan Tamil (SJKT) di daerah Petaling, Selangor. Hasil kajian mendapati bahawa terdapat tiga faktor amalan pentadbiran yang menjadi penghalang kepada guru untuk memainkan peranan sebagai agen perpaduan etnik di sekolah. Pertama, sistem pengasingan guru dalam dua sesi persekolahan; kedua, pengelompokan guru di bilik guru mengikut mata pelajaran; dan ketiga, tumpuan utama kepada sukatan pelajaran berbanding dengan aspek lain seperti perpaduan etnik di sekolah. Kajian ini mendapati bahawa ketiga-tiga faktor ini menyumbang kepada kewujudan jurang etnik sesama guru, sekali gus menjadi penghalang kepada peranan guru sebagai agen sosialisasi politik dalam membentuk perpaduan etnik yang berkesan di sekolah. Justeru, pihak sekolah perlu memberi perhatian terhadap isu ini dan memberi kesedaran kepada semua warga sekolah tentang kepentingan perpaduan etnik di institusi tersebut.